Altitudinal Variation in Trap-Based Abundance of Bactrocera dorsalis in Red Chili Fields of West Sumatra, Indonesia - Nguyễn, Phước Sang; Novri Nelly; Reflinaldon (Universitas Andalas, 2026)
Altitudinal gradients strongly influence the distribution and abundance of insect pests by affecting microclimate, host availability, and cropping intensity. Bactrocera dorsalis (Hendel) is a major constraint to red chili (Capsicum annuum L.) production in Indonesia; however, empirical evidence linking altitude to its field abundance in Sumatra has not been fully elucidated. This study quantified the association between altitude and the abundance patterns of B. dorsalis using field data collected from 33 chili-growing sites across four regencies of West Sumatra, Indonesia, spanning elevations from <15 to 1,571 m above sea level, during the rainy season (October 2024-March 2025). Adult flies were monitored using methyl eugenol-baited modified Lynfield traps. Catch data were analyzed across altitudinal zones using ANOVA, correlation, and linear regression. Trap catches differed significantly among elevation categories (p< 0.05), with higher mean abundance generally recorded in pre-montane sites (>600 m) than in lowland sites (<600 m). Regression analysis indicated a positive association between altitude and trap catches (r = 0.391, p = 0.024), with altitude explaining 15.3% of the variation in abundance (R2 = 0.153), and linear regression indicated a moderate increase in captures with increasing elevation (B = 0.103). K-means clustering of regencies based on mean elevation and total trap catches further separated Solok as a distinct group characterized by higher abundance. These findings demonstrate spatial structuring of B. dorsalis abundance across elevation zones and support the incorporation of elevation-informed surveillance into fruit fly monitoring programs in West Sumatra.